As above, so below? The influence of leader humor on bootleg innovation: The mechanism of psychological empowerment and affective trust in leaders - Zheng, Xiong; Mai, Sheng; Zhou, Chunguang; Ma, Liang; Sun, Xiaomeng (Frontiers in Psychology, 2022)
Leadership humor is widely used in management practice and has aroused extensive discussion in academia. On account of the two-sided influence of leader humor on employees, its double-edged sword effect on employee behavior has been put more emphasis. As a benign violation of organizational norms and a kind of pro-organizational violation respectively, both Leadership humor and employee bootleg innovation have the characteristics of violating organizational norms, but few studies have examined the relationship between them. Based on benign violation theory and social cognition theory, this study conducted a two-stage questionnaire survey and statistical-econometric analysis of 324 employees in 23 IT and manufacturing technology companies in Guangdong, Jiangsu, Zhejiang, Hubei, Beijing and Shanghai, China. It not only examined the relationship between leadership humor and employee bootleg innovation but also tested a moderated mediation model. Results show that leadership humor is positively correlated with psychological empowerment and employee bootleg innovation, namely, leadership humor indirectly and positively affects employee bootleg innovation through psychological empowerment. Moreover, the indirect effect is positively regulated by leadership emotional trust. The higher the emotional trust of employees to leadership, the stronger the mediating role of psychological empowerment between leader humor and bootleg innovation behavior. The study enriches the existing path of research on the double-edged impact of leader humor on employee behavior, expands the boundary conditions of the relationship between empowered cognitive mediation and employee bootleg innovation and provides enlightenments for Chinese leaders to effectively apply the tool of leader humor.